Consumption tax and corporate product mix decisions - Ghosh, Pulak; Jacob, Martin; Kang, Ya; Zhang, Jian (Journal of Accounting and Economics, 2026)
This paper investigates the effect of frictions in consumption taxes on firms' product mix decisions. We use a stacked difference-indifferences approach that exploits the staggered transition from a sales tax with the risk of tax cascading to a value added tax (VAT) with credits on inputs across states in India, as well as detailed data on listed manufacturing firms' production decisions. We find that the switch to a VAT system induces affected firms to narrow their product scope and to reduce vertical integration. That is, firms cut the internal production of input goods and instead focus their production on their best-performing products. Firms affected by the switch to VAT reduce their firm size and are more likely to outsource production of input goods. We also show that this vertical disintegration results in lower manufacturing costs, higher profitability and firm value, and increased investment efficiency for affected firms. Overall, the paper shows that alleviating frictions in sales tax or VAT systems can reduce investment and productivity distortions and improve the allocation of capital across firms.